The effectiveness of University of Wisconsin solution on prolonged myocardial protection as assessed by phosphorus 31-nuclear magnetic resonance spectroscopy and functional recovery - Karck, Matthias; Vivi, Aantonio; Tassini, Maria; Schwalb, Herzl; Askenasy, Nadir; Navon, Gil; Borman, Joseph B.; Uretzky, Gideon (The journal of thoracic and cardiovascular surgery, 1992)
The effectiveness of the University of Wisconsin solution on extended myocardial preservation was examined in this study using phosphorus 31-nuclear magnetic resonance spectroscopy. Isolated perfused rat hearts were arrested and stored in four preservation solutions: group 1, modified Krebs-Henseleit solution; group 2, modified St. Thomas' Hospital solution; group 3, oxygenated modified St. Thomas' Hospital solution containing 11 mmol/L glucose; and group 4, University of Wisconsin solution. The changes in myocardial high energy phosphate profiles and the intracellular pH values were measured during 12 hours of cold (4 degrees C) global ischemia and 90 minutes of normothermic reperfusion. Following ischemia, the hearts were assessed for hemodynamic recovery and myocardial water content. During ischemia, adenosine triphosphate depletion was observed in all groups; however, after 5 hours of ischemia, the adenosine triphosphate levels were significantly higher in group 3 compared with the other groups (adenosine triphosphate levels at 6 hours in mumol/gm dry weight: group 3, 7.6; group 4, 3.2; group 2, < 1; p < 0.025). The tissue water content at the end of ischemia was lower with the University of Wisconsin solution compared with the modified St. Thomas' Hospital solution or the oxygenated modified St. Thomas' Hospital solution (in ml/gm dry weight: group 4, 3.0; group 2, 4.4; group 3, 3.9; p < 0.05). The adenosine triphosphate repletion during reperfusion was greater with the University of Wisconsin solution compared with the modified St. Thomas' Hospital solution or the oxygenated modified St. Thomas' Hospital solution (12 mumol/gm dry weight in group 4; 8.1 in group 2; 9.0 in group 3; p < 0.05). Similar findings were obtained for the recovery of left ventricular pressure (in percent of preischemic control: group 4, 70%; group 2, 42%; group 3, 52%; p < 0.01) and coronary flow (group 4, 61%; group 2, 49%; group 3, 49%; p < 0.05). These data suggest that preservation with the University of Wisconsin solution affords improved hemodynamic recovery, enhanced adenosine triphosphate repletion, and reduced tissue edema upon reperfusion; however, oxygenated St. Thomas' Hospital solution with glucose is associated with the preservation of higher myocardial adenosine triphosphate levels during prolonged cold global ischemia. In conclusion, these data indicate that the University of Wisconsin solution might improve graft tolerance of ischemia in clinical heart transplantation.